A new vision of women in Islamic jurisprudence A critical analytical study - Ahmed Mahmoud Ahmed (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
It is obvious that sharia law, all the celestial religions, and civil laws have significantly concerned about the humans’ safety for this reason a numerous procedure have been conducted including Physical punishment and financial punishment (financial penalty) to decrease crime, deter the criminal, and provide protection to oppressed person. One of the disputes and controversial focus or issue is blood money which includes blood money for dead person, or blood money for someone who infringes on another member of other family, Islamic law is pioneer in this area. What attracts attention is most of Islamic scholars have differentiated between blood money for male and female. However, the differentiation between blood money for male and female have not relied on accurate principle. Therefore, the current study aims to illustrate this issue subjectively based on the academic and legal prove through academic debates, prove of scholars and their responses based on the Sharia Law, rules and fixed principles.